Oral branched-chain amino acids supplementation in athletes: A systematic review - Martinho, D. V.; Nobari, H.; Faria, A.; Field, A.; Duarte, D.; Sarmento, H. (Nutrients, 2022)
Branched-chain amino acids (BCAAs) are oxidized in the muscle and result in stimulating anabolic signals—which in return may optimize performance, body composition and recovery. Meanwhile, among athletes, the evidence about BCAA supplementation is not clear. The aim of this study was to review the effects of BCAAs in athletic populations. The research was conducted in three databases: Web of Science (all databases), PubMed and Scopus. The inclusion criteria involved participants classified both as athletes and people who train regularly, and who were orally supplemented with BCAAs. The risk of bias was individually assessed for each study using the revised Cochrane risk of bias tool for randomized trials (RoB 2.0). From the 2298 records found, 24 studies met the inclusion criteria. Although BCAAs tended to activate anabolic signals, the benefits on performance and body composition were negligible. On the other hand, studies that included resistance participants showed that BCAAs attenuated muscle soreness after exercise, while in endurance sports the findings were inconsistent. The protocols of BCAA supplements differed considerably between studies. Moreover, most of the studies did not report the total protein intake across the day and, consequently, the benefits of BCAAs should be interpreted with caution.